Assessing the Performance of PNP Reservoir Based on Short-Term Rainfall Data in the Upper Kuranji Watershed, Padang, Indonesia - Nofra Masdaf; Fauzan; Bambang Istijono; Revalin Herdianto (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2025)
This study was conducted to assess the performance of the PNP Reservoir in managing water resources as well as reducing flood risk in the Batu Busuk Sub-watershed, which is located in the upstream part of the Kuranji watershed, Padang City. The uniqueness of this study lies in the comprehensive approach that combines IDF analysis with three methods (Talbot, Sherman, and Ishiguro), flood discharge estimation through the Rational and Nakayasu SUH methods, and modeling of reservoir inflows and outflows using the Muskingum flood routing method. Based on the results of the IDF analysis, the highest rain intensity during the two-hour duration was recorded at 27.22 mm/hour (Talbot), 24.67 mm/hour (Sherman), and 23.49 mm/hour (Ishiguro). Before the reservoir was constructed, the peak flood discharge reached 0.33 m³/sec at 0.35 hours. The simulation results showed that the reservoir was able to reduce the peak discharge by 0.57% and caused a delay in the peak flow of 0.6 minutes. This finding shows that the PNP reservoir contributes positively to flood control, although the efficiency of the reduction is still limited. Overall, the results of this study can serve as an important reference in the design of adaptive reservoirs in areas characterized by steep topography and high rainfall, and emphasize the role of reservoirs as part of sustainable flood mitigation infrastructure in tropical urban areas.